Pop Perspectives : Readings to Critique Contenporary Culture - Laura Gray-Rosendale (McGraw Hill Higher Education, 2007)
This book teaches essential academic skills using a contemporary, pop-cuture-centered approach. students learn about the tools of critical reading and writing and how to use them with the cultural touchstones they come across every day. By examining the products of pop culture, students will gain greater insight into not just writing, but their world at large.